Enantioselective Copper-Catalyzed Reductive Coupling of Vinylazaarenes with N-Boc Aldimines - Choi, Bonnie; Saxena, Aakarsh; Smith, Joshua J.; Churchill, Gwydion H.; Lam, Hon Wai (Synlett, 2015)
The diastereo- and enantioselective reductive coupling of vinylazaarenes with N-Boc aldimines is described. The reactions proceed using chiral copper–bisphosphine complexes in the presence of TMDS as a hydride source to give reductive coupling products in moderate to high enantioselectivities.
Keywords: asymmetric catalysis; copper; enantioselectivity; imines; vinylazaarenes